Exploring the potential of expatriate social networks to reduce HIV and STI transmission: a protocol for a qualitative study - Crawford, Gemma; Bowser, Nicole; Brown, Graham; Maycock, Bruce (B M J Group, 2013)
Introduction HIV diagnoses acquired among Australian men working or travelling overseas including Southeast Asia are increasing. This change within transmission dynamics means traditional approaches to prevention need to be considered in new contexts. The significance and role of social networks in mediating sexual risk behaviours may be influential. Greater understanding of expatriate and traveller behaviour is required to understand how local relationships are formed, how individuals enter and are socialised into networks, and how these networks may affect sexual intentions and behaviours. This paper describes the development of a qualitative protocol to investigate how social networks of Australian expatriates and long-term travellers might support interventions to reduce transmission of HIV and sexually transmitted infections. Methods and analysis To explore the interactions of male expatriates and long-term travellers within and between their environments, symbolic interactionism will be the theoretical framework used. Grounded theory methods provide the ability to explain social processes through the development of explanatory theory. The primary data source will be interviews conducted in several rounds in both Australia and Southeast Asia. Purposive and theoretical sampling will be used to access participants whose data can provide depth and individual meaning. Ethics and dissemination The role of expatriate and long-term traveller networks and their potential to impact health are uncertain. This study seeks to gain a deeper understanding of the Australian expatriate culture, behavioural contexts and experiences within social networks in Southeast Asia. This research will provide tangible recommendations for policy and practice as the findings will be disseminated to health professionals and other stakeholders, academics and the community via local research and evaluation networks, conference presentations and online forums. The Curtin University Human Research Ethics Committee has granted approval for this research.